2017
DOI: 10.18520/cs/v113/i05/938-941
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Tribological of <i>Argemone</i> Biodesel Sunthesized Using Microwave Techinquee

Abstract: Microwave technique was applied for the synthesis of Argemone biodiesel from Argemone oil under defined experimental conditions. The method presented has the potential to synthesize quality biofuel in timeefficient manner. It also results in higher yield of biodiesel while decreasing the reaction time by almost 75% when compared with conventional heating method. The biodiesel produced was tested for various physico-chemical properties and found to maintain the quality as recommended by various specifications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Fatima et al tested A. ochroleuca, reaching the biodiesel conversion of 91% (w/w) after a 120 min reaction, at 65 • C and using a 7:1 methanol-to-oil molar ratio [27]. Agarwal et al reported a significant reaction time reduction (almost 75%) using microwave-assisted heterogeneously catalyzed transesterification compared with conventional transesterification [28].…”
Section: Introductionmentioning
confidence: 99%
“…Fatima et al tested A. ochroleuca, reaching the biodiesel conversion of 91% (w/w) after a 120 min reaction, at 65 • C and using a 7:1 methanol-to-oil molar ratio [27]. Agarwal et al reported a significant reaction time reduction (almost 75%) using microwave-assisted heterogeneously catalyzed transesterification compared with conventional transesterification [28].…”
Section: Introductionmentioning
confidence: 99%